The Prevalence of Overweight and Obesity in an Adult Kuwaiti Population in 2014 - Weiderpass, Elisabete; Botteri, Edoardo; Longenecker, Joseph C.; Alkandari, Abdullah; Al-Wotayan, Rihab; Al Duwairi, Qais; Tuomilehto, Jaakko (Frontiers in Endocrinology, 2019)
Background: According to WHO estimates, Kuwait is ranked amongst the top countries in the world in obesity prevalence. This study aims to describe the prevalence of overweight, obesity and various types of adiposity in Kuwaiti adults. Methods: This cross-sectional study of 3,915 Kuwaiti adults aged 18 to 69 years used the STEP-wise approach to surveillance of non-communicable diseases, a WHO Instrument for Chronic Disease Risk Factor Surveillance. We assessed demographic information, lifestyle, personal and family history of diseases and physical measurements (height, weight, waist and hip circumferences). All participants with valid height and weight measurements (n=3,589) were included in the present analysis. Overweight was defined as BMI 25-29.9 kg/m2 and obesity as BMI ≥30 kg/m2. Results: Obesity prevalence was 40.3% [95% confidence interval, 38.6-42.0%] (men, 36.5%; women, 44.0%); and overweight prevalence was 37% [35.4-38.7%] (men, 42%; women, 32.1%). The median BMI was 28.4 kg/m2 among men and 29.1 kg/m2 among women. Obesity prevalence was directly associated with female sex, age, history of diabetes and being married in both men and women; and was inversely associated with education level in women. The prevalence of elevated waist-to-hip ratio was 46.9% among men and 37.9% among women. Waist circumference, waist-hip and waist-height ratios were inversely associated with education, work status and cardiovascular disease in women and with diabetes history in both men and women. Conclusion: Almost eight in ten Kuwaiti adults were overweight or obese. Urgent public health action is warranted to tackle the obesity epidemic in Kuwait.